Diagnostic utility of total adenosine deaminase as a biomarker in patients with transudates from pleural effusion syndrome - Maranhão, Bernardo Henrique Ferraz; Silva Junior, Cyro Teixeira da; Barillo, Jorge Luiz; Souza, Joeber Bernardo Soares de; Silva, Patricia Siqueira; Stirbulov, Roberto (ABCS Health Sciences, 2025)
Introduction: Accurately identifying pleural fluid as either transudate or exudate is critical. P-ADA, or the total pleural adenosine deaminase enzyme, is a reliable biomarker for distinguishing between transudates and exudates. Objective: This study aimed to identify P-ADA diagnostic parameters for pleural transudate diagnosis by establishing a cutoff value using the receiver operating characteristic curve. Methods: The P-ADA assay was performed using a kinetic technique. The performance of the model was evaluated using the area under the receiver operating characteristic curve (AUC-ROC) and diagnostic parameters. The ideal cutoff value for P-ADA in pleural transudates was determined using the Youden index in the ROC curve. Results: A total of 157 patients with exudative pleural effusion (n=124, 79%) and transudative pleural effusion (n=33, 21%) were included in this observational retrospective cohort study. The optimal cutoff value of P-ADA was ≤8.21 U/L. The diagnostic parameters as sensitivity, specificity, positive and negative predictive values, positive and negative likelihood values, odds ratio, and accuracy were 66.0 (95% CI, 0.48-0.82); 81.0 (95% CI, 0.73-0.87); 48.0 and 90.0 (95% CI, 0.33-0.64; 0.83-0.94); 4.9 and 0.56 (95%CI, 2.21-11.2; 0.39-0.82); 8.78 (95%CI, 0.78-18.34), and 78.0 (95%CI, 0.80-0.91), respectively (chi-square=29.51, p=0.00001). The AUC was 0.8203 (95% CI, 0.7270-0.8838); SE, 0.0393; Z-value to test, 8.157; p<0.0001. An AUC >0.75 was clinically useful. The Hosmer-Lemeshow test showed excellent discrimination. Conclusion: P-ADA levels can be used to obtain reliable diagnostic and predictive parameters for discriminating between transudative and exudative pleural effusions.